2019
DOI: 10.1093/ibd/izz294
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Adalimumab With an Immunomodulator Is Not More Effective Than Adalimumab Monotherapy in Children With Crohn’s Disease: A Post Hoc Analysis of the PAILOT Randomized Controlled Trial

Abstract: Background The PAILOT trial was a randomized controlled trial aimed to evaluate proactive vs reactive therapeutic drug monitoring in children with Crohn’s disease (CD) treated with adalimumab. Our aim in this post hoc analysis of the PAILOT trial was to assess the efficacy and safety of adalimumab combination treatment in comparison with monotherapy at week 72 after adalimumab induction. Methods Participants were children 6–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…9 There is limited data regarding the immunogenicity to ADL from studies on children with IBD. ADAs to ADL have been re-ported to occur in 3.3% to 10.3% of pediatric patients, 21,22 which is a relatively lower proportion than that observed among their counterparts receiving IFX and also among adult patients with IBD. The absence of ADAs against ADL observed in our study could be due to the significantly shorter duration of anti-TNF treatment in patients treated with ADL compared with those receiving IFX (0.9±0.5 years vs 3.0±1.3 years; p<0.001).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…9 There is limited data regarding the immunogenicity to ADL from studies on children with IBD. ADAs to ADL have been re-ported to occur in 3.3% to 10.3% of pediatric patients, 21,22 which is a relatively lower proportion than that observed among their counterparts receiving IFX and also among adult patients with IBD. The absence of ADAs against ADL observed in our study could be due to the significantly shorter duration of anti-TNF treatment in patients treated with ADL compared with those receiving IFX (0.9±0.5 years vs 3.0±1.3 years; p<0.001).…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile, a recent study of children with CD revealed that there was no benefit of adding an immunomodulator to ADL treatment compared with ADL monotherapy. 22 Further large-scale and longitudinal studies on the impact of concomitant treatment with an immunomodulator during treatment with ADL in children are required for better insight. Therapeutic drug monitoring (TDM) of anti-TNF agents has emerged as a strategy to optimize and personalize treatment based on measurement of TLs and ADAs.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the bene ts of the combined use of immunomodulators with ADA are controversial [19][20][21][22][23][24]. Although there was no association between the concomitant use of immunomodulators with ADA versus only ADA in this study (P = 0.252), we found that AAA positivity was signi cantly lower in the immunomodulator combination group (1/27 [3.7%] vs. 11/25 [44%], P < 0.05, Mann-Whitney's U-test).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the benefits of the combined use of immunomodulators with ADA are controversial [19][20][21][22][23][24]. In this study, although there was no association between the concomitant use of immunomodulators with ADA and only ADA (P = 0.252), AAA positivity was significantly lower in the immunomodulator combination group than in the immunomodulator non-combination group (1/27 [3.7%] vs. 11/25 [44%], P <0.05, Mann-Whitney U test).…”
Section: Plos Onementioning
confidence: 99%